Synthesis and Evaluation Antibacterial Activity of Some New Substituted 5-Bromoisatin Containing Five, Six Heterocyclic Ring - Baghdad Science Journal (مجلة بغداد للعلوم, 2016)
This research includes the synthesis of some new different heterocyclic derivatives of 5-Bromoisatin. New sulfonylamide, diazine, oxazole, thiazole and 1,2,3-triazole derivatives of 5-Bromoisatin have been synthesized. The synthesis process started by the reaction of 5-Bromoisatin with different reagents to obtain schiff bases of 5-Bromoisatin intermediate compounds(1, 8, 19) by using glacial acetic acid as a catalyst in three routes. The first route, 5-Bromoisatin reacted with p-aminosulfonylchloride to product compound(1), then converted to sulfonyl amide derivatives(2-7) by the reaction of compound(1) with different substituted primary aromatic amine in absolute ethanol. The second route includes the reaction of 5-Bromoisatin reacted with ethyl glycinate to give 5-bromo-3-(Ethyl imino acetate)-2-oxo indole(8), which undergo react with hydrazine hydrate 80% to obtain hydrazine derivatives(9) that react with different acid anhydrides to obtain diazine derivatives(10-14). Also compound(8) reacts with urea and thiourea to give compounds(15,16) which undergo cyclization with p-bromophenacylbromide in absolute ethanol as a solvent to obtain oxazole (17) and thiazole (18), respectively. The third route included the reaction of 5-Bromoisatin with p-phenylenediamine in ethanol to obtain compound(19) which is converted to new substitutes 1,2,3-triazole derivatives(22,23) by diazotation of compound(19) and treating the resulted salt(20) with sodium azid, then acetylaceton or ethylacetoacetate, respectively. Newly synthesized compounds were identified by spectral methods. (FTIR, 1H-NMR, 13C-NMR) and measurements of some of its physical properties and also some specific reactions. Furthermore the effects of the synthesized compounds were studied on some strains of bacteria.